INVESTIGATION OF UBIQUITOUS-PHYSICS APP WITH LEARNING GUIDED MAP TO FACILITATE PHYSICS LEARNING IN AUTHENTIC CONTEXTS - Purba, Siska Wati Dewi; Hwang, Wu-Yuin (Polyglot, 2022)
Many studies have considered the use of mobile devices to support learning in different subjects such as English, math, and biology. However, there are not many studies which focus on facilitating physics learning with mobile device supports in authentic contexts. Taking this into account, we updated a mobile app called Ubiquitous-Physics (U-Physics) by adding a guide learning map (gMap) which helps students to explore inclined plane phenomena in authentic contexts. We aimed to investigate the effectiveness of U-Physics with gMap on students’ learning achievements and to analyze students’ perceptions based on interview results. Forty-five first-grade vocational high school students majoring in housekeeping management were participated in this quasi-experiment for seven weeks. The experimental group used U-Physics with gMap and the control group used U-Physics without gMap. Although there were no significant differences between the experimental group and the control group concerning learning achievements, we found that learning gain of both groups significantly improved. Additionally, students revealed that they enjoyed exploring and conducting physics experiments in authentic context environments such parks, playgrounds, and houses. These findings indicated that exploring and conducting physics phenomena in authentic contexts can enhance understanding of the physics phenomena and enriches experiential learning.Bahasa Indonesia Abstrak Banyak penelitian telah mempertimbangkan penggunaan perangkat seluler untuk mendukung pembelajaran dalam berbagai mata pelajaran seperti bahasa Inggris, Matematika, dan Biologi. Namun, tidak banyak penelitian yang berfokus pada memfasilitasi pembelajaran Fisika dengan dukungan perangkat seluler dalam konteks otentik. Dengan mempertimbangkan hal ini, kami memperbarui aplikasi seluler bernama Ubiquitous-Physics (U-Physics) dengan menambahkan peta pembelajaran panduan (gMap) yang membantu siswa menjelajahi fenomena bidang miring dalam konteks otentik. Kami bertujuan untuk menyelidiki efektivitas U-Physics dengan gMap pada prestasi belajar siswa dan untuk menganalisis persepsi siswa berdasarkan hasil wawancara. Empat puluh lima siswa sekolah menengah kejuruan, kelas satu, jurusan manajemen rumah tangga berpartisipasi dalam percobaan semua ini selama tujuh minggu. Kelompok eksperimen menggunakan U-Physics dengan gMap dan kelompok kontrol menggunakan U-Physics tanpa gMap. Meskipun tidak ada perbedaan yang signifikan antara kelompok eksperimen dan kelompok kontrol mengenai prestasi belajar, kami menemukan bahwa perolehan pembelajaran kedua kelompok meningkat secara signifikan. Selain itu, siswa mengungkapkan bahwa mereka senang menjelajahi dan melakukan eksperimen Fisika di lingkungan konteks otentik seperti taman, taman bermain, dan rumah. Temuan ini menunjukkan bahwa mengeksplorasi dan melakukan fenomena Fisika dalam konteks otentik dapat meningkatkan pemahaman tentang fenomena Fisika dan memperkaya pembelajaran berdasarkan pengalaman.